Pragmatic Analysis of Language Politeness & FTA/FSA Strategies in The East Java Gubernatorial Debate 2024 - Asrori, Hadi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Political debates in regional head elections serve not only as a platform for the exchange of ideas but also as a reflection of the communication strategies employed to build image and garner public sympathy. In this context, the selection of words and modes of expression becomes paramount, particularly in upholding ethics and language politeness. This study aims to analyze the forms of language politeness in the East Java Gubernatorial Election debate of 2024 using a pragmatic approach. The primary focus of this research is on Leech's (1983) politeness principles, which encompass six maxims: “Tact Maxim”, generosity, appreciation, modesty, agreement, and sympathy, as well as identifying their violations. Furthermore, this research examines Face Threatening Acts (FTA) and Face-Saving Acts (FSA) based on Brown & Levinson's (1987) theory. The methodology employed is qualitative descriptive, utilizing observation and note-taking techniques on the transcripts of three debate sessions. The results indicate that of the 67 data instances, Candidate Pair 1 (Luluk–Lukman) predominantly adhered to the “Tact Maxim” and generosity, Candidate Pair 2 (Khofifah–Emil) excelled in the maxims of appreciation and modesty, while Candidate Pair 3 (Risma–Hans) exhibited a greater tendency towards the maxims of agreement and sympathy. Various forms of FTA and FSA were also identified, reflecting each candidate's communication strategy in constructing their political image. This study reinforces the significance of politeness and pragmatic strategies in political discourse as a means of maintaining harmony, strengthening identity, and ethically influencing public opinion.